Application of the Rehabilitation Principle of "GU ZHENG (Bones Integrity) and JIN HE (Muscles Harmony), XING SHEN GONG TIAO (Union of Body and Mind)" in Chronic Musculoskeletal Dysfunction - WANG Xiangbin; HOU Meijin; GOU Yanyun; XU Yang; LIN Ziling; TAO Jing (康复学报, 2023)
Chronic musculoskeletal dysfunction involves all parts of the body, affecting the patients' motor function, daily acti-vities and quality of life. The main pathogenesis of musculoskeletal disorders is the imbalance of muscles and bones, the disharmony of body and mind, and the specific manifestations are the physical disorders, including bone disintegrity, discord of muscles and tendons, as well as emotion-cognition and motor-coordination disorders. "GU BU ZHENG (bones disintegrity) "manifests as malalignment of joints and abnormal bone metabolism, affecting the joint motion, stability and boby control abilities, resulting in arthralgia, stiffness and other dysfunctions; "JIN BU HE (discord of muscles and tendons)" manifests as changes of muscle tone, mass and strength, abnormal coordination between muscle groups and imbalance of muscle metabolism, resulting in weakness, atrophy, spasm, etc. "XING SHEN SHI TIAO (the disunion of body and mind)" demonstrates as dysfunction of emotion-cognition, and the neuromuscular motor control, resulting in abnormal control of joints and muscles, and the function of body and mind is difficult to correspond well. The imbalance of muscles and bones and disharmony of body and mind affect each other. According to the principle of musculoskeletal rehabilitation, combined with the understanding of the functions of GU (bones and joints), JIN (muscles and tendons), XING (body) and SHEN (mind) in traditional Chinese medicine (TCM) in rehabilitation, the authors put forward the rehabilitation principle of "GU ZHENG JIN HE, XING SHEN GONG TIAO". "GU ZHENG-bones integrity" means that maintaining good alignment of the joints and keeping normal bone metabolism balance. "JIN HE-harmony of muscles and tendons" indicates that the related muscle groups, ligaments and other soft tissues around the joints have good flexibility, balanced tone and strength, and the muscle groups play a coordinated role in motion and stability. Meanwhile, the muscle metabolism is normal, that is, the shape, quality and function of muscles and tendons are maintained in a harmonious state. The function of Gu is to provide structural support and stability. "Bone integrity makes the body robust", which is complemented by the function of muscles and tendons to drive joint movements, stabilize and coordinate joint movements — "harmonious muscles keeps the body healthy". "XING SHEN GONG TIAO-union of body and mind" refers to the correct control of the nervous system on joint movements, muscle activation and coordination, as well as the good coordination of emotion and cognition with bone integrity and muscles harmony, which reflects the importance of body and mind uniformity in promoting motor control ability to the balance of muscles and bones, so as to achieve "regulating the mind to control the body" and "strengthening the body to modulate the mind". Moreover, TCM rehabilitation therapies, such as traditional exercises, acupuncture and moxibustion, Tuina, etc., all reflect the importance of the balance of muscles and bones, and the body and mind."GU ZHENG (bone integrity) and JIN HE (muscles harmony), XING SHEN GONG TIAO (union of body and mind)" is the embodiment of the integrated functional concept of TCM rehabilitation. It is also the active rehabilitation principle applicable to musculoskeletal dysfunction, which helps give play to the advantages of targeted rehabilitation and the characteristics of holistic rehabilitation with integrated traditional Chinese medicine and western medicine.